A review on mechanisms and models for the churn-turbulent flow regime. (17th February 2016) - Montoya, Gustavo; Lucas, Dirk; Baglietto, Emilio; Liao, Yixiang
Abstract: The modeling of two-phase flows has always been limited to special cases due to the very complex nature of its interface. When considering vertical pipe flows with low gas volume flow rates, bubbly flow occurs. With increasing gas volume flow rates larger bubbles are generated by bubble coalescence, which further leads to transition to slug, churn-turbulent, and annular flow. Considering, as an example, a heated tube producing steam by evaporation, as in the case of a vertical steam generator, all these flow patterns including transitions are expected to occur in the system. Despite extensive attempts, robust and accurate simulations approaches for such conditions are still lacking. This paper summarizes the state-of-the-art on the understanding of the physics behind churn-turbulent flow, and transitions to and from this flow pattern. Both, benefits and limitations of the existent experimental approaches and their usefulness for model development and validation at these high void fraction conditions are discussed. Limitation of both, low-dimensional approaches (0D, 1D, and 2D), and high resolution approaches such as Direct Numerical Simulations (DNS) are analyzed. Averaging procedures, such as the Eulerian–Eulerian approach including the interfacial momentum closures which has been used in the past for simulating churn flow, are review thoroughly. Finally, possible improvements are proposed. Graphical abstract: